2019
DOI: 10.1126/scitranslmed.aau9242
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir (GS-5734) protects African green monkeys from Nipah virus challenge

Abstract: Nipah virus is an emerging pathogen in the Paramyxoviridae family. Upon transmission of Nipah virus from its natural reservoir, Pteropus spp. fruit bats, to humans, it causes respiratory and neurological disease with a case-fatality rate about 70%. Human-to-human transmission has been observed during Nipah virus outbreaks in Bangladesh and India. A therapeutic treatment for Nipah virus disease is urgently needed. Here, we tested the efficacy of remdesivir (GS-5734), a broad-acting antiviral nucleotide prodrug,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
172
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 19 publications
1
172
0
2
Order By: Relevance
“…Remdesivir, an adenosine analogue that can target the RNA-dependent RNA polymerase and block viral RNA synthesis, which has been a promising antiviral drug against a wide array of RNA viruses (including SARS/MERS-CoV 5) infections in cultured cells [58], mice [59] and nonhuman primate models [60,61]. The Washington Department of Health administrated remdesivir intravenously firstly and found that remdesivir might have potential protection from SARS-CoV-2 infection [62].…”
Section: Virally Targeted Inhibitorsmentioning
confidence: 99%
“…Remdesivir, an adenosine analogue that can target the RNA-dependent RNA polymerase and block viral RNA synthesis, which has been a promising antiviral drug against a wide array of RNA viruses (including SARS/MERS-CoV 5) infections in cultured cells [58], mice [59] and nonhuman primate models [60,61]. The Washington Department of Health administrated remdesivir intravenously firstly and found that remdesivir might have potential protection from SARS-CoV-2 infection [62].…”
Section: Virally Targeted Inhibitorsmentioning
confidence: 99%
“…Ebola virus (EBOV)) (5,8) and Paramyxoviridae (e.g. Nipah virus (NiV)) families (7,10,11), as well as in vitro activity against viruses in the Pneumoviridae (e.g. respiratory syncytial virus (RSV)) family (10).…”
mentioning
confidence: 99%
“…Remdesivir (GS-5734) is a nucleotide prodrug that has broad antiviral activity against viruses from different families in vitro (4), and therapeutic efficacy in nonhuman primate models of lethal Ebola virus and Nipah virus infection (5,6). Studies in human airway epithelial cells showed that remdesivir also inhibits replication of a wide range of coronaviruses, including MERS-CoV (7).…”
mentioning
confidence: 99%